USE OF FINANCIAL ACCOUNTING DATA IN PROCESS OF BUSINESS DECISION-MAKING ON MEDIUM AND SMALL ENTERPRISES IN INDIA - Ahmed Mgadami, Shafik Yousef; Himah Musa, Ali Albasheer (The journal of contemporary issues in business and government, 2022)
The demand for projecting and evaluating the effects of administrative decisions increases as the business continues to undergo transformation. A technique for future examination of a company’s economic reports is employed to support and assess such judgments. The format and substance of a company’s accounting documents have changed significantly in contemporary decades. The concepts of organisation and the procedures for reporting and auditing are changing drastically along with the expansion of economic interactions. At worldwide accountancy’ conventions as well as other expert gatherings, the topic of changing a company’s accounting records is frequently brought up. The goal of the project is to advance the idea of creating accounting information for a business to use as a basis for informational decision-making in a changing economic environment. This research tries to emphasise the logic in the economic decision making of the Medium and small scale enterprises (MSEs) financial management which either results to optimization in the financing operations of the MSEs or collapses. In order to study the economic managerial discretion of MSEs in India, numerous parameters had already been recognised. An organised survey has been created and researched on 257 innovators and finance experts of MSEs in northern India. This one was discovered that there is a correlation and influence between demographic characteristics and firm-specific considerations, financial behaviour, financial skills, and revenue growth way of measuring on the economic managerial actions. The study finds that the accounting records summary has a significant impact on how effectively managers make decisions. The management choices made by MSEs enterprises are greatly influenced by other processing parameters such organizational records, the clarity of analyses, and the quality management. The study found that a favourable association among economic accountancy statements and appropriate strategies is mediated by the economic statements’ clarity, applicability, and reliability